Scenario analysis for integrated water resources management under future land use change in the Urmia Lake region, Iran. (January 2020) - Shirmohammadi, Bagher; Malekian, Arash; Salajegheh, Ali; Taheri, Bahram; Azarnivand, Hossein; Malek, Ziga; Verburg, Peter H.
Abstract: Arid and semi-arid regions are particularly vulnerable to global environmental change because of their fragile climatic conditions. The rapid development of land use is expected to affect aquatic ecosystems in these regions. In this study, we focused on how land use change affects the stream flow and inflow to Urmia Lake in the Mordagh Chay basin, Iran. This case-study exemplifies dynamics found across a much larger region. We mapped changes in land use between 1993–2015 using satellite imagery and modeled future changes using the Dyna-CLUE model. We projected future land use change until 2030 under four scenarios: continuing of the current trend of water use, 40% water withdrawal reduction, and two other scenarios with 40% water withdrawal reduction and improvements of irrigation efficiency up to 50% and 85%. Between 1993–2015, 21% of the study area changed to orchard and arable land mostly at the cost of rangeland. However, upon reduction of water withdrawal our analyses showed that garden must decrease between 27% and 40%. Rainfed cropland is projected to experience a major increase in all scenarios, especially in the case of reduced water withdrawal, where it will increase by 217%. In order to achieve sustainable water resources management land use plays a major role and leads to different land use futures in this type of semi-arid regions.